Chromium Tricarbonyl and Chromium Benzene Complexes of Graphene, Their Properties, Stabilities, and Inter‐Ring Haptotropic Rearrangements – A DFT Investigation. Issue 2 (2nd December 2014) - Gloriozov, Igor P.; Marchal, Rémi; Saillard, Jean‐Yves; Oprunenko, Yuri F.
Abstract: The structures, electronic properties, stabilities, mechanisms, and activation barriers of the intramolecular inter‐ring haptotropic rearrangements (η 6, η 6 ‐IRHRs) of chromium tricarbonyl and chromium benzene complexes of graphene were modeled by DFT calculations. All of the above calculated characteristics are in good agreement with the experimental data for related complexes with ultralarge, large, and medium‐sized polyaromatic ligands (PALs). Generally η 6, η 6 ‐IRHRs between isomer complexes with organometallic groups (OMGs) in different positions in graphene ligand proceeds via η 3 ‐transition states with activation barriers considerably lower (<25 kcal/mol) than those of the corresponding rearrangements in medium‐sized PALs (>30 kcal/mol). This could be explained by the reduction of electron density and the increase of electron mobility inside graphene molecules, which weaken metal–ligand bonds and facilitate rearrangements. Abstract : DFT calculations show that organometallic moieties such as Cr(CO)3 or Cr(benzene) can move easily on large polyaromatic hydrocarbons.